2003
DOI: 10.1073/pnas.2533829100
|View full text |Cite|
|
Sign up to set email alerts
|

Bacillus subtilisRecU protein cleaves Holliday junctions and anneals single-stranded DNA

Abstract: Bacillus subtilis RecU protein is involved in homologous recombination, DNA repair, and chromosome segregation. Purified RecU binds preferentially to three- and four-strand junctions when compared to single-stranded DNA (ssDNA) and double-stranded DNA (dsDNA) (≈10- and ≈40-fold lower efficiency, respectively). RecU cleaves mobile four-way junctions but fails to cleave a linear dsDNA with a putative cognate site, a finding consistent with a similar genetic defect observed for genes classified within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
136
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(146 citation statements)
references
References 34 publications
10
136
0
Order By: Relevance
“…4A). The sequence recognized by RecU on this arm of synthetic HJ-J3 was 5Ј-GG2CT-3Ј that is in good agreement with the previously published consensus recognition site for RecU (36). No symmetric cleavage of HJ-J3 DNA was observed in the denaturing gel (Fig.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…4A). The sequence recognized by RecU on this arm of synthetic HJ-J3 was 5Ј-GG2CT-3Ј that is in good agreement with the previously published consensus recognition site for RecU (36). No symmetric cleavage of HJ-J3 DNA was observed in the denaturing gel (Fig.…”
Section: Resultssupporting
confidence: 90%
“…We previously observed that RecU cleavage was often uncoupled in a synthetic HJ if the RecU consensus recognition sequence (5Ј-(G/T)G2C(A/C)-3Ј) is not present in the two opposite arms, and that the absence of RecU impairs chromosomal segregation (32,36). When the cleavage of HJ-J3 DNA by RecU was analyzed on denaturing PAGE, preferentially a nick on one arm (arm 4) was observed (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations